Sistem Absensi Pegawai Berbasis Android dengan Teknologi Geolocation pada Lingkungan Pemerintah Daerah Kabupaten Sarolangun - Ahmad Husna Ahadi; Gustina (Prodi Teknik Informatika (S1) Institut Teknologi dan Bisnis Indonesia, 2023)
Technological advances on smartphones, especially the geolocation feature, have now been developed to carry out various kinds of innovations. One of the innovations made is an Android-based attendance system. Many government or private agencies have implemented this Android-based attendance system in their organizations. This is because the existence of an android-based attendance system will make it easier to record employee attendance and can minimize the occurrence of fraud in recording attendance. Several agencies in the Sarolangun Regency Government are currently still using a manual attendance system which causes delays in data collection because they have to do manual recaps. This study aims to build an android-based attendance system that is tailored to the environmental needs of the Sarolangun district government. It is hoped that this system can reduce the problems that occur and make it easy for employees to take attendance via their respective smartphones.